Hubungan Antara Kelincahan dan Koordinasi Mata-Kaki dengan Kemampuan Menggiring Bola Pemain Sepak Bola di SMP Negeri 10 Kerinci - Cundra Bahar (Journal on Education, 2023)
This research originated from the low dribbling ability in the football game of SMP Negeri 10 Kerinci students. The problem is caused by many factors including agility and eye-foot coordination. The purpose of this study was to find out whether there is a relationship between agility and eye-foot coordination with the dribbling ability of football players at SMP Negeri 10 Kerinci. This type of research uses correlational. The population is all members of the SMP Negeri 10 Kerinci football team as many as 25 players. Samples are taken with the entire population, Data retrieval techniques using tests. To measure agility using a back and forth running test with a distance of 4x10 meters, for the eye-foot coordination variable using the eye-foot coordination target test and for the dribbling variable with a zigzag dribbling test past the seat as many as 5 pieces. The data analysis techniques used are: product moment techniques and multiple correlations. The results showed that there was a significant relationship between agility and dribbling ability obtained tcount 2.696 > ttable 1.71 with correlation results or r = 0.490. For the second hypothesis there is a significant relationship between eye-foot coordination and dribbling ability obtained tcount 2.137 > ttable 1.71 with correlation results or r = 0.407. Furthermore, there is a significant relationship between agility and eye-foot coordination together with the dribbling ability of football players at SMP Negeri 10 Kerinci obtained Fcalculate 5.34 > Ftable 3.44 with correlation results or r = 0.249.